Preparation and characterization of green polymer by copolymerization of corn oil and sulphur at molten state - Abbasi, A. (SAGE Publications Ltd, 2021)
Vegetable oils are a promising class of bioresources for producing green polymeric materials to reduce the dependence on petro-based polymers. In this study, a green copolymer prepared by thermal copolymerization corn oil with sulphur at its molten state is reported for the first time. The proportions of sulphur to corn oil (w/w) in the reaction mixture were varied in the range of 50/50 to 80/20 and the reactions were carried out at 170Â°C for 1 h. The obtained copolymers were characterized using Fourier transform infrared (FTIR), thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and powder X-ray diffraction (PXRD). The percentage of the unsaturated fatty acid portion was found to act as a multifunctional monomer stabilizing polysulphide forming crosslinked structures that vary depending on reactant sulphur content. The obtained copolymers were found to be amorphous thermosets with heavily crosslinked structures and composite morphologies. The copolymers also showed high thermal stability under nitrogen atmosphere. The new copolymers are environmentally friendly hybrid material promoting green chemistry with a potential added value to abundantly available sulphur and corn oil. Â© The Author(s) 2020.